2008
DOI: 10.1080/17290376.2008.9724917
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related needs for safety among male-to-female transsexuals (mak nyah) in Malaysia

Abstract: This research, commissioned by the Malaysian AIDS Council in 2007, is qualitative and descriptive in nature. In depth face-to-face interviews were carried out with 15 mak nyah respondents from five major towns. The interviews were guided by an interview schedule that had seven main topics: brief background; hormone-taking behaviour; safe sex; health care; substance abuse; harassment from authorities; and HIV prevention. The HIV problem among the mak nyah, mak nyah sex workers and their clients is critical. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…These groups have been marginalized through a process of stigmatization, discrimination, and criminalization [ 7 10 ]. As in most countries, sex work is criminalized in Malaysia [ 11 ], leaving CWSWs and TWSWs vulnerable to physical and sexual abuse from legal authorities. Structural conditions also leave TWSWs and CWSWs vulnerable to economic instability [ 12 – 14 ], with research highlighting that transgender women often experience difficulties entering stable forms of employment due to lack of qualifications and discrimination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These groups have been marginalized through a process of stigmatization, discrimination, and criminalization [ 7 10 ]. As in most countries, sex work is criminalized in Malaysia [ 11 ], leaving CWSWs and TWSWs vulnerable to physical and sexual abuse from legal authorities. Structural conditions also leave TWSWs and CWSWs vulnerable to economic instability [ 12 – 14 ], with research highlighting that transgender women often experience difficulties entering stable forms of employment due to lack of qualifications and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Structural conditions also leave TWSWs and CWSWs vulnerable to economic instability [ 12 – 14 ], with research highlighting that transgender women often experience difficulties entering stable forms of employment due to lack of qualifications and discrimination. Poverty inhibits sex workers’ use of condoms with clients [ 11 , 15 17 ]; evidence has shown that many sex workers acquiese to requests from clients to not use condoms in exchange for higher payments [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though the total number of TGW in Malaysia is unknown, an estimated 21,000 TGW engage in sex work, with 37.5% of them residing in greater Kuala Lumpur (Lim, Ang, & Teh, 2010); HIV prevalence among all TGW is estimated at 10% (Ministry of Health Malaysia, 2013). While some literature has highlighted the need for HIV prevention and advocacy services for mak nyah (Teh, 2008a) , there is otherwise limited recent research available, particularly surrounding how their identity influences access to and engagement in healthcare generally and specifically for HIV prevention and treatment services.…”
Section: Background On Malaysiamentioning
confidence: 99%
“…They encounter immense hardship to secure gainful employment and in order to survive, some of them resorted to involve in sex work. As a result, they are exposed to the high risk of HIV infection (Teh, 2008) and other sexually transmitted diseases. According to the Human Rights Watch's report in 2017, legal criminalisation and public discrimination have caused transsexuals to avoid public health facilities and as a result, HIV prevalence among the transsexual individuals is estimated at 5.6% as compared to 0.4% among the general population.…”
Section: Introductionmentioning
confidence: 99%